Performing Art and Culture Center Hamdan - N. Vinky Rahman; Esra Monica Aruan (Talenta Publisher, 2019)
Performing Art and Culture Center is a building that functions as a center of activity to accommodate the creativity of the community in the field of art as well as public space facilities in the city of Medan. The center for arts and culture is expected to be able to respond to the problem of Medan City in providing community space and informal education facilities so that this function aims as a community space that can accommodate artistic activities with adequate facilities. The method used in designing this project is a data collection through field surveys and literature studies. This project is one of the functions in the revitalization of the Integrated Hamdan Area in Medan Maimun District. To reflect the concept of revival and as an innovative design, the theme of this project is contemporary architecture. This project will be a non-formal education facility that is educational and entertaining. With this function, Performing Arts and Culture can increase tourism in Medan, a place to create value for the creativity of the community, increase the sensitivity of the people of Medan city towards traditional and modern cultural arts, and make Medan a cultured city.